On the asymptotics of integral manifolds of singularly perturbed systems with delay - Cherevko, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the problem of constructing asymptotic decompositions of integral manifolds of slow variables for linear and nonlinear singularly perturbed systems with delay.